Contrasting tracheal, bronchus, and lung cancer burdens and care quality: a comparative analysis of China and global trends - Xiuquan Lin; Shiwen Liu; Yating Ding; Jianhui Zhao; Fei He; Wenling Zhong (BMC Cancer)
Abstract Background This study aims to explore the temporal trends of tracheal, bronchus, and lung cancer burden in Fujian Province, China, and globally. Additionally, it evaluates changes in attributable risk factors and the quality of care. Methods Based on data from the Fujian Provincial Center for Disease Control and Prevention and the Global Burden of Disease (GBD), the age-standardized rates (ASRs) of incidence, death, and disability-adjusted life years (DALY) were collected and analyzed. Joinpoint regression analysis and age-period-cohort models were used to estimate temporal trends, and principal component analysis was used to estimate the quality-of-care index (QCI). Results In 2019, the ASRs of incidence, death, and DALYs were 39.08, 35.29, and 778.39 per 100,000 population in Fujian Province, respectively. From 1990 to 2019, ASRs increased, with average annual percent changes (AAPCs) of 1.08% (95% confidence interval [CI]: 0.77–1.38%), 0.65% (95% CI: 0.35–0.95%), and 0.18% (95% CI: -0.07–0.42%), respectively. The burden sharply increased after age 50 and the ASRs of incidence, death, and DALY in males in Fujian Province were all over 3-folds higher than in females. However, females burden showed increasing trend from 2015 to 2019. Compared with 1990, age‑standardized DALY rates attributable to ambient particulate matter pollution increased markedly, whereas those attributable to household solid fuel use declined. Moreover, we founded that QCI increased with age. The temporal trends indicated decrease in QCI from 1990 to 2019. Conclusion The burden of tracheal, bronchus, and lung cancer in Fujian Province remained significant. Smoking, secondhand smoke, and ambient particulate matter pollution were the main risk factors. The quality of care for patients needed improvement. Graphical Abstract